Preparation and Study of Zinc Oxide Nanoparticles to Evaluate TheirAntioxidant Activity - A. Shatti, Wafaa; A.Hassan, N. (ASJ - Academic Science Journal, 2025)
Zinc oxide nanoparticles were prepared by chemical reaction method, which is one of the methods that does not require high temperatures during preparation. The prepared particles were tested by X-ray diffraction (XRD) spectroscopy and UV-vis spectroscopy (FESEM) was performed and the antioxidant behavior of ZnO nanoparticles was evaluated by free radical scavenging of 2,2-diphenyl-1-picrylhydrazyl hydrate ( DPPH) at different nanoparticle concentrations and a discrete time interval. The DPPH scavenging activity was monitored by UV spectrophotometry and ZnO nanoparticles showed good antioxidant activity.